2007
DOI: 10.1155/2007/72497
|View full text |Cite
|
Sign up to set email alerts
|

Selenopentathionic and Telluropentathionic Acids as Precursors for Formation of Semiconducting Layers on the Surface of Polyamide

Abstract: The layers of copper chalcogenides, which were formed on the surface of semihydrophilic polymer—polyamide 6 (PA) using monoselenopentathionicH2SeS4O6and monotelluropentathionicH2TeS4O6acids as precursors of chalcogens, were characterized. Fourier transform infrared (FT-IR) and UV spectroscopy were used to monitor the effect of chalcogens on the changes in structure of PA corresponding to the concentration of the precursor's solution and an exposure time. The IR spectra of modified PA were completely different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…These precursors are more beneficial than conventional sources due to their higher stability. It was determined that, under our experimental conditions, the solution of monotelluropentathionic acid was more stable than the alkaline metal salt solution of a similar concentration [26] used in our previous experiment.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…These precursors are more beneficial than conventional sources due to their higher stability. It was determined that, under our experimental conditions, the solution of monotelluropentathionic acid was more stable than the alkaline metal salt solution of a similar concentration [26] used in our previous experiment.…”
Section: Introductionmentioning
confidence: 74%
“…The selection of suitable precursors and their studies illustrate how chalcogens' compounds could be used in electroactive materials. The preparation of chalcogen layers using chalcopolythionic acids, such as monoselenopentathionic H 2 SeS 4 O 6 and monotelluropentathionic H 2 TeS 4 O 6 , has caught the attention of researchers [20,25,26]. These precursors are more beneficial than conventional sources due to their higher stability.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of sulfur-containing particles sorbed by a PA film was studied by means of IR and UV absorption spectra of the polymer films treated in a potassium telluropentathionate [15] and the telluropentathionic acid [17] solutions. These investigations have confirmed that telluropentathionate anions sorb-diffuse into PA treated with the solutions of telluropentathionates.…”
Section: Resultsmentioning
confidence: 99%
“…These precursors are more beneficial than conventional sources due to their higher stability. It was determined that under our experimental conditions, the solution of monotelluropentathionic acid was more stable than its alkaline metal salt solution of a similar concentration [26] that has been used in our previous experiment.…”
Section: Introductionmentioning
confidence: 86%
“…The selection of suitable precursors and their studies illustrate, how chalcogens' compounds could be used in the electroactive materials. The preparation of chalcogen layers using chalcopolythionic acids, such as monoselenopentathionic H2SeS4O6 and monotelluropentathionic H2TeS4O6, has caught the attention of researchers [20,25,26]. These precursors are more beneficial than conventional sources due to their higher stability.…”
Section: Introductionmentioning
confidence: 99%